Pengaruh Komunikasi Terapeutik Terhadap Kepuasan Pasien Di Ruang Rawat Inap Salah Satu Rumah Sakit Sawasta di Yogyakarta - Tarigan, Lady Agitha; Oktri Hastuti, Agustina Sri; Widianti, Christina Ririn (STIKes Panti Rapih, 2023)
Abstract Background: Therapeutic communication is one of the activities where nurses assist patients in overcoming the problems experienced and emotional to achieve patient recovery. Objective : to determine the correlation of nurse therapeutic communication against inpatient satisfaction in the nursing room at the Santa Elisabeth Hospital. Methods : Correlative descriptive method, using a cross sectional approach, purposive sampling was carried out from March to July 2021 with 47 respondents using a questionnaire, and data analysis using the Spearmen correlation test through SPSS. Results :univariate analysis, mostly 23 (53.4%) patients said that therapeutic communication was in the poor category and most of the patients' satisfaction as many as 27 (67.4%) were in the low category. The results of the bivariate analysis obtained a significance number or probability number 0.003 <0.05, then there is an influence of therapeutic communication on patient satisfaction in the Inpatient Room of Santa Elisabeth Hospital. Conclusion : There is a relationship between nurses' therapeutic communication and the satisfaction of inpatients in Santa Elisabeth Hospital. Suggestion: as an evaluation material and also input in providing useful nursing services to improve the quality of hospital services